The Effect of Financial Condition, Audit Tenure, and Previous Year's Audit Opinion on Going Concern Audit Opinions on Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2018: Pengaruh Kondisi Keuangan,Audit Tenure, dan Opini Audit Tahun Sebelumnya Terhadap Opini Audit Going Concern Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2016-2018 - Febrianti, Adela; Rahmawati, Imelda Dian (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to determine the effect of financial conditions, audit tenure, and previous year's audit opinion on going concern audit opinions. The sample used in this study were manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018 and the number was 32 companies. This study uses multiple linear regression analysis techniques using SPSS for windows. Based on the results of the study, financial condition significantly affects going concern audit opinion, audit tenure does not significantly affect going concern audit opinion, while the previous year's audit opinion has a significant effect on going concern audit opinion.